Atypical fibroxanthoma of the cheek—case report with dermatoscopy and dermatopathology - Mike Inskip (Mattioli1885, 2014)
We present a case report of an atypical fibroxanthoma on the cheek of a 73-year-old man. Clinical, dermatoscopic and dermatopathologic images are presented.